Multiplatform calculations of atomic radiative properties in Hf VI. (May 2023) - Motoumba, E. Bokamba; Yoca, S. Enzonga; Quinet, P.; Palmeri, P.
Highlights: The transition rates have been computed for 185 E1 transitions in Hf VI falling in the spectral range from 193 Å to 474 Å. A multiplatform approach has been used to assess the accuracy of the computed transition rates of the Hf VI spectrum. The strong lines (S ≥ 1 a.u.) have accuracies ranging from a few percents to ~40%. Abstract: In order to compute the Hf VI radiative rates and estimate their accuracy, a multiplatform approach has been adopted to calculate the oscillator strengths and transition probabilities for the 185 E1 transitions in Hf VI as classified in 2014 by Ryabtsev et al. (Phys Scr 2014;89:11502). It consisted of three independent atomic structure models; one based on the semi-empirical HFR method and two based on the ab initio MCDHF method. It was found that most of the Hf VI atomic states are strongly mixed with purity less than 50 %. This causes the computed rates to be highly model-sensitive with uncertainties of more than 100 % for most of the weak lines with line strength S < 1  a.u. For the strong E1 transitions with S ≥ 1  a.u., their accuracies range between a few percents and ∼ 40 % . Finally, we recommend our HFR rates except for the two lines at 223.172 Å and at 231.451 Å where the transition rates of Ryabtsev et al. should be used instead, although their uncertainties are greater than 50 % . It is due to strong cancellation effects affecting our calculation for these two transitions.